Här kan jag vara mig själv och här finns det plats att utvecklas : En kvalitativ studie om geografiska platser och identitetsutveckling - Jerome, Alexandra (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
Globalization in today's societies has resulted in many individuals around the world being able to identify themselves as world citizens. However, Sweden's different locations and regions are both what individuals take for granted as well as what most Swedes call home. Identity development is something that is constantly happening in humans as an active actor, but what it is that influences a certain type of development is not as obvious. Often there is a link between who you are as an individual and where this individual has grown up, which indicates a reciprocity between location and identity development. One requires the other. A geographic location can be a nation, region, city, or neighborhood. Geographical locations also contribute to a sense of identity, such as property, ownership and community that defines the individual or group's identity in the form of a sense of belonging. Identifying with a certain geographic location can produce a certain perception of the location that in turn may affect how individuals develop their own identity. The aim of the study was to investigate: "How geographical locations are understood in relation to identity creation and identity development in Luleå Municipality". From this point of view, four research questions are derived; “What is the connection between an individual's identity and its place of residence?” “What influences individuals' choice of residence? “What are the conditions and expectations for different geographical locations?” “How do respondents discuss culture, norms and values regarding different geographical locations?” The study has a qualitative approach where women between 20-30 years of age have been interviewed to find out their opinion about the study. The geographical location common to the respondents in this study is Luleå county, half of the respondents have grown up in Luleå while the rest have moved up from another geographical location to Luleå to study at the University of Technology in Luleå. The results based on current theoretical ...